INDIAN METHOD OF ACTING: A COMPREHENSIVE RESEARCH ANALYSIS :MANISH JOSHI - Joshi, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The Indian method of acting, deeply rooted in classical treatises such as Natya Shastra and evolving through regional theatre traditions, combines emotional expression (rasa), physical gestures (abhinaya), and spiritual discipline. This paper provides an in-depth study of the Indian method of acting, including historical context, core principles, and modern adaptations. Special attention is given to the contributions of Prasanna Hegdu, whose work synthesizes traditional and contemporary acting techniques to create a uniquely Indian acting methodology relevant for modern theatre and cinema.